Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

given g(x) = -x + 4 solve for x when g(x) = 0

Sagot :

Answer:

[tex]x=4[/tex]

Step-by-step explanation:

-x + 4 equals 0.

Substitute 4 for x:

[tex]g(4)=-4+4[/tex]

Simplify:

[tex]g(4)=0[/tex]

[tex]x=4[/tex]